A fuzzy approach to the balance of drop and delay priorities in differentiated services networks. - Runtong Zhang (IEEE Transactions on fuzzy systems)
Two of the objectives of Internet are to increase network capacity and offer high quality of differentiated services for traffic with real-time and nonreal-time requirements. Differentiated services (Diff-Serv) were established to fulfill such objectives. Up until now, several Diff-Serv schemes have been proposed which, among others, handle drop and delay priorities. These two priorities raise important optimization issues for the Internet but their relationship remains an open problem. This paper presents a fuzzy control algorithm to select packets in a fair and efficient manner. Simulation shows that the fuzzy controller is better than a crisp one when the fairness issue is raised.